Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11064-011-0499-x
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Ruby is Rapidly Taken up by Neurons and Astrocytes in Organotypic Brain Slices

Abstract: Cholinergic neurons are intensively studied, because they degenerate in Alzheimer's disease. Although neurotracer techniques are widely used to study axonal transport, guidance, regeneration or sprouting it is not clear if cholinergic neurons can be stained by tracer techniques and studied in brain slices. The aim of the present study was to evaluate the characteristics of the neurotracer Miniruby in organotypic brain slices of the basal nucleus of Meynert (nBM), focusing on cholinergic neurons. Miniruby is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several applications have been reported, such as e.g. repeated multi-electrophysiological recordings and stimulations (Egert et al, 1998; Jahnsen et al, 1999; Karpiak and Plenz, 2002; Dong and Buonomano, 2005), or gene transfer techniques (Ridoux et al, 1995; Thomas et al, 1998; Murphy and Messer, 2001), retrograde tracing using fluorescent dyes (Ullrich and Humpel, 2011), or long-term live imaging (Gogolla et al, 2006). Organotypic brain slices can be analyzed using all common neurobiological methods.…”
Section: Methodological Aspects Using the Membrane Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Several applications have been reported, such as e.g. repeated multi-electrophysiological recordings and stimulations (Egert et al, 1998; Jahnsen et al, 1999; Karpiak and Plenz, 2002; Dong and Buonomano, 2005), or gene transfer techniques (Ridoux et al, 1995; Thomas et al, 1998; Murphy and Messer, 2001), retrograde tracing using fluorescent dyes (Ullrich and Humpel, 2011), or long-term live imaging (Gogolla et al, 2006). Organotypic brain slices can be analyzed using all common neurobiological methods.…”
Section: Methodological Aspects Using the Membrane Techniquementioning
confidence: 99%
“…The method was modified and optimized by Stoppini et al (1991), who found that organotypic brain slices survive well when cultured on semipermeable membranes. Meanwhile, this method has been used and adapted by several research groups including ours (Bergold and Casaccia-Bonnefil, 1997; Noraberg, 2004; De Simoni and Yu, 2006; Marx, 2010; Ullrich et al, 2011; Ullrich and Humpel, 2011; Shamir and Ewald, 2014). As an attractive alternative the in oculo model was developed, which allows three-dimensional tissue grafts in the anterior eye chamber to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Voltage-Sensitive (FluoVolt) and Calcium-Sensitive (Rhod-4) Dyes Fluorescently labeled dextrans are frequently employed in live cell imaging studies to track both anterograde and retrograde neuronal pathways, a technique firmly established in our laboratory [28]. MiniRuby (Invitrogen, Thermo Fisher Scientific, Waltham, MA, USA, D3312) is a dextran conjugate combined with the red-fluorescent dye tetramethylrhodamine.…”
Section: Live Cell Imaging With Neurotracer (Miniruby)mentioning
confidence: 99%
“…Zhang et al, (2003) described these cells as CSF-contacting tanycytes in the ventral ventricular wall. In the literature, only glia at the site of injection of BDA was labeled with the neuronal tracer (Rajakumar et al, 1993), Mini-ruby, a member of the dextran family, labeled astrocytes in organotypic slices of the brain (Ullrich and Humpel, 2011). However, Wouterlood and Jorritsma-Byham, (1993) noted in a few cases that BDA-labelled glial or perivascular cells were identified in the injection area but the labelling of glial cells in other sites did not occur.…”
Section: Csf-contacting Neurons Projections Destinate Otr-expressing ...mentioning
confidence: 99%